Electronic distance learning satisfaction, awareness, attitudes, and barriers among undergraduate nursing students following the october 7 war in Palestine - Ashraf Jehad Abuejheisheh; Rabia H. Haddad; Wafaa J. Tohol; Salam Bani Hani (PLoS ONE, 2026)
Background Education is one of the many facets of daily life that have been severely interrupted by the ongoing conflict in Palestine since October 7, 2023. Assessing the efficacy and difficulties of electronic distance learning (EDL) requires an understanding of undergraduate nursing students’ experiences with it during this period. Aim The study aimed to assess the levels of satisfaction, awareness, attitudes, preferences, and barriers towards EDL distance learning among undergraduate nursing students during the war. Methods A descriptive cross-sectional design was used. A valid and reliable self-administered questionnaire was utilized to assess the levels of satisfaction, awareness, attitudes, preferences, and barriers toward EDL among undergraduate nursing students. Results A total of 292 nursing students participated in this cross-sectional study. Participants demonstrated an overall positive attitude toward EDL (M = 3.02, SD = 0.529), particularly regarding flexibility and ease of use. However, overall satisfaction with EDL was low (M = 2.84, SD = 0.885), revealing a clear contrast between favorable perceptions and actual learning satisfaction. Most students (80.9%) were aware of EDL. Infrastructural barriers were the most prominent challenges, with electricity shortages (64.7%), high internet costs (62.7%), and poor connectivity (61.6%) dominating the EDL experience. Satisfaction levels differed significantly by sex, age group, and digital tool used; however, causal inferences are limited due to the cross-sectional design. Conclusion The study's findings highlight how crucial it is to continue planning and coming up with solutions that both fill in the gaps in EDL and capitalize on its benefits. The educational institution decision-makers should give this issue a top priority and create a blended learning system to improve communication between instructors and students. Taking into account the security of students during pandemics and wars.